THE ROLE OF ADAPTIVE EMOTION REGULATION IN MEDIATING THE CORRELATION BETWEEN FORGIVENESS AND STUDENTS' LEVELS OF DEPRESSIVE SYMPTOMS - Aji, Nawang Purbo; Sunawan, Sunawan (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Adolescents have a higher risk of experiencing depressive disorders due to fluctuating emotional changes in adolescence. Therefore, further studies exploring predictors that can help reduce symptoms of depressive disorders in adolescents are essential. This study examines the relationship between forgiveness and depression through the mediating role of adaptive emotion regulation strategies (mindfulness, reappraisal, and problem solving). This study used a correlational design involving 358 Senior High School adolescents from Boyolali Regency. Multiple mediation analysis was conducted using a bias-corrected (N=5000) bootstrapping technique [CI 95%] using PROCESS model 4 syntax to explain the role of adaptive emotion regulation strategies as mediators. Based on the results of the analysis, a significant negative relationship was found between forgiveness and depression, as well as between the three adaptive emotion regulation strategies and depression. However, forgiveness was positively correlated with all three adaptive emotion regulation strategies. The mediation analysis showed that the three adaptive emotion regulation strategies negatively affected the relationship between forgiveness and depression (? =-0.68, p<0.01). The results of this study confirmed the mediating role of adaptive emotion regulation strategies in the relationship between forgiveness and depression. Thus, to help adolescents reduce depression levels, counselors are recommended to strengthen adaptive emotion regulation strategies as a complement to forgiveness skills.